Spatial and Seasonal Studies of Sedimentological and Neoichnological Characteristics from Mangrove areas of Karachi, Pakistan - Noor Us Saher; Naureen Aziz Qureshi; Asmat Saleem (International Journal of Economic and Environmental Geology, 2016)
The purpose of this study is to appraise the physicochemical properties of mangrove sediments and their influence on neoichnological properties produced by different crab species from Korangi Creek (S1) and Sandspit backwater areas (S2 and S3), Karachi. The significant spatial, seasonal and tidal differences (p <0.05) were examined in %moisture, %porosity and sorting coefficient Φ.The significant spatial and seasonal variations were observed in total organic matter, mean Φ, skewness Φ and kurtosis Φ of sediment. Neoichnological properties (burrow number, diameter and total burrow opening area) were observed with significant differences among the macrohabitat (stations) and microhabitat (tidal levels). The correlation analysis indicated that the neoichnological properties are strongly linked with sedimentological properties such as water contents, total organic matter and textural parameters. This study could be employed to distinguish between different paleoenvironmental controlling factors, predicated on similar paleoichnological features made by similar fossil organisms in a mangrove environment. Keywords: Mangrove sediment, grain size composition, ichnology, Karachi, Pakistan